Metáfora conceptual e ideologia: o caso do discurso das políticas de austeridade na imprensa portuguesa - Augusto Soares da Silva (Revista Investigações)
This work studies the metaphorical conceptualization of austerity policies in the Portuguese press and its ideological purpose. The analysis relies on a corpus of news and opinion articles published in June-July 2011, after the entry of the Troika, and May 2013, when protests against the austerity policies intensified. The analysis reveals the persuasive and manipulative force of certain specific metaphors, such as obesity/diet, indebted family, good student, and sacrifice. These socially-embodied metaphors are grounding in moral cultural models and serve ideological, emotional and moral purposes.